(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Ceremonies play a pivotal role in the continuance of the human interaction. The Indigenous ceremonies are considered to be sacred and they bring people together for various occasions. It is distinct and remarkable for each community. The locale of the ceremony becomes colourful with rituals, songs, music, dance, feasts and giveaways. The ceremonies also play a crucial role in withholding the traditional knowledge and practices and also gets transmitted to its posterity. The present paper analyses the importance of ceremonies and its constituents and also exhibits the association of the Canadian Natives in their native environment.